2012
DOI: 10.5539/jas.v4n4p103
|View full text |Cite
|
Sign up to set email alerts
|

Potential and Challenges in Use of Thermal Imaging for Humid Region Irrigation System Management

Abstract: Thermal imaging has shown potential to assist with many aspects of irrigation management that include scheduling application of water and detecting leaking irrigation canals and delivery systems. There are particular challenges for use of thermal imaging for scheduling irrigation in humid subtropical climates, which include the need for fine delineation of canopy temperatures under low vapor pressure deficits, proper accounting for micrometeorological conditions, and altitude effects on canopy temperature repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…The results obtained by Baluja et al [51] and Gago et al [50] showed that all three thermographic indices are well correlated with the stomatal conductance measured directly on the ground (with coefficients of determination (R 2 ) ranging from 0.54 up to 0.70). Thomson et al [76] discuss the potential and challenges involved in using thermal methods for sensing canopy temperature in humid subtropical climates, where small increases in canopy temperature can be difficult to detect. They also demonstrate the effect of altitude (in their experiment, altitude accounted for 58% of the variability in canopy temperature), and validate the use of thermal imagery to detect leakage from irrigation systems.…”
Section: Vegetation Indicesmentioning
confidence: 99%
“…The results obtained by Baluja et al [51] and Gago et al [50] showed that all three thermographic indices are well correlated with the stomatal conductance measured directly on the ground (with coefficients of determination (R 2 ) ranging from 0.54 up to 0.70). Thomson et al [76] discuss the potential and challenges involved in using thermal methods for sensing canopy temperature in humid subtropical climates, where small increases in canopy temperature can be difficult to detect. They also demonstrate the effect of altitude (in their experiment, altitude accounted for 58% of the variability in canopy temperature), and validate the use of thermal imagery to detect leakage from irrigation systems.…”
Section: Vegetation Indicesmentioning
confidence: 99%
“…Remote sensing technology has been widely used and developed in agriculture and can provide a rapid, cost‐effective method for assessing crop injury caused by glyphosate drift. Studies using a convenient agricultural aircraft platform for remote sensing have been documented for weed discrimination and CHL‐a detection in catfish ponds, and studies using thermal imagery have been reported for water stress, zonal soil suitability and irrigation system diagnostics …”
Section: Introductionmentioning
confidence: 99%
“…Studies using a convenient agricultural aircraft platform for remote sensing have been documented for weed discrimination and CHL-a detection in catfish ponds, 21 and studies using thermal imagery have been reported for water stress, zonal soil suitability and irrigation system diagnostics. 22 Henry et al 23 indicated that multiple indices formulated from the band information extracted from hyperspectral reflectance could distinguish between healthy and injured soybean and corn plants to which herbicides, glyphosate and paraquat had been applied. Huang et al 24 examined the effect of glyphosate drift from aerial application on non-GR cotton by spray drift sampling and aerial multispectral remote sensing.…”
Section: Introductionmentioning
confidence: 99%
“…Wet areas should show a lower radiance temperature as compared to drier areas during sunny day hours, whereas the opposite is expected after the sunset and before the dawn [4]. Thermal infrared (TIR) sensors are used on this basis to assess the soil moisture or the evaporation rate over vegetation canopy areas [5][6][7][8][9][10][11][12]. However, the detection accuracy of the TIR [5,6,10] is low leading to false positives and misinterpretations caused by diverse scenarios like dense vegetation or shadows.…”
Section: Introductionmentioning
confidence: 99%